Image of the Month: Clinical Features in a Newborn with Covered Cloacal Exstrophy - Vilanova-Sánchez, Alejandra; Ching, Christina B.; Gasior, Alessandra C.; Diefenbach, Karen; Wood, Richard J.; Levitt, Marc (European Journal of Pediatric Surgery Reports, 2017)
Cloacal exstrophy is the most severe type of anorectal malformations that belongs to the bladder–exstrophy–epispadias complex of genitourinary malformations. Interestingly, its variant, the covered cloacal exstrophy, is often missed. The clinical findings of this variant may include an imperforate anus, low lying umbilicus, thick pubic bone, and pubic diastasis but with an intact abdominal wall. We present an interesting case of covered cloacal exstrophy with a side-by-side duplicated bladder and discuss important considerations for the time of colostomy creation in the newborn period.
Keywords: covered cloacal exstrophy; variant; anorectal malformation; bladder duplication